KEPERCAYAAN DIRI DAN KECERDASAN MENGASIHI (LOVING INTELLIGENCE): KOMPETENSI GURU PAUD INKLUSI MASA KINI - Triana Lestari; Nenden Ineu Herawati (UPI Kampus Cibiru, 2018)
Abstract:. This research stems from the latest phenomenon about the low results of the Teacher Competency Test as an impact of the teacher's lack of confidence in making teaching patterns according to student needs. The teacher's view of the quality of themselves and the ability to build relationships with students is the basis of this research, especially the belief that it is difficult to teach students with special needs. This study aims to look at the personal and social competencies of prospective teacher students as seen from their relationship / teacher-student relations with children with special needs in the inclusive school setting. The research method used was action research with a subject of 73 students of PAUD teacher candidates. Measurement uses a STRS (Student-Teacher Relationship Scale) instrument, to identify the level of relationship between prospective teacher and student students, especially students with Special Education Need (SEN). The results of the study indicate the low quality of student teacher relations with students, especially students with special needs in inclusive classes, this is reflected in the high conflict, high dependence beliefs and low aspects of closeness.Keywords: Self-confidence, Loving Love, Inclusive Teacher Abstrak: Penelitian ini bermula dari fenomena terkini tentang rendahnya hasil Uji Kompetensi Guru sebagai dampak dari minimnya kepercayaan diri guru untuk membuat pola pengajaran sesuai dengan kebutuhan siswa. Pandangan guru terhadap kualitas diri dan kemampuan membangun hubungan dengan siswa, menjadi landasan penelitian ini dilakukan, terutama keyakinan sulitnya mengajar siswa dengan berkebutuhan khusus. Penelitian ini bertujuan untuk melihat kompetensi pribadi dan sosial mahasiswa calon guru yang terlihat dari hubungannya/ teacher-student relation dengan anak-anak berkebutuhan khusus di setting sekolah inklusi. Metode penelitian yang digunakan adalah penelitian tindakan dengan subjek sebanyak 73 mahasiswa calon guru PAUD. Pengukuran menggunakan instrumen STRS (Student-Teacher Relationship Scale), untuk mengidentifikasi tingkat hubungan mahasiswa calon guru dan siswa terutama siswa dengan Special Education Need (SEN). Hasil penelitian menunjukkan rendahnya kualitas hubungan mahasiswa calon guru dengan siswa terutama siswa berkebutuhan khusus dalam kelas inklusif, hal ini tercermin pada tingginya konflik, keyakinan ketergantungan yang tinggi dan aspek kedekatan yang rendah.Kata Kunci: Kepercayaan diri, Kecerdasan mengasihi, Guru Inklusif